KETIKA BIAS GENDER MENGKRISTAL; MEMPERTANYAKAN PERAN PENDIDIKAN ISLAM - Zulkifli Rusby (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This paper discusses the phenomenon of strengthening the culture of patriarchy that so long rooted in Islamic education process. In the process of education for example, are in the form of drawings in which the topic of haughty (arrogant) described a group of women who were talking about a woman who overbearing. That during this time the role of women have been cornered by misrepresents the moral values of Islam by scholars in part. This cornered position, has been so strong both the role of women in the political area, in terms of liberating education process, and in terms of interpretation and the hadiths of the Prophet Muhammad. Therefore, the emergence of gender bias in the interpretation of Islamic education came from scholars who tend to provide a significant opportunity for the defense of the masculine; among them is the issue of polygamy, inheritance of women, and women's leadership.